2020
DOI: 10.3389/fgene.2020.578712
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Landscape During Skeletal Muscle Differentiation

Abstract: Cellular commitment and differentiation involve highly coordinated mechanisms by which tissue-specific genes are activated while others are repressed. These mechanisms rely on the activity of specific transcription factors, chromatin remodeling enzymes, and higherorder chromatin organization in order to modulate transcriptional regulation on multiple cellular contexts. Tissue-specific transcription factors are key mediators of cell fate specification with the ability to reprogram cell types into different line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 115 publications
0
13
0
Order By: Relevance
“…The changing chromatin landscape has also been analyzed during OPC differentiation (Castelo-Branco and Liu, 2020 ) and mutations in chromatin modifiers, such as CHD7 and CHD8, have a profound effect on the formation of OLs from OPCs (Marie et al, 2018 ). Given the now widespread appreciation of the relationship between chromatin status and differentiation in multiple tissues (for example in skeletal muscle; Hernández-Hernández et al, 2020 ), this is not a surprising finding, but it nevertheless underscores epigenetic regulation as another field of ongoing research regarding OPCs (Gregath and Lu, 2018 ).…”
Section: Transcriptomic Technologiesmentioning
confidence: 88%
“…The changing chromatin landscape has also been analyzed during OPC differentiation (Castelo-Branco and Liu, 2020 ) and mutations in chromatin modifiers, such as CHD7 and CHD8, have a profound effect on the formation of OLs from OPCs (Marie et al, 2018 ). Given the now widespread appreciation of the relationship between chromatin status and differentiation in multiple tissues (for example in skeletal muscle; Hernández-Hernández et al, 2020 ), this is not a surprising finding, but it nevertheless underscores epigenetic regulation as another field of ongoing research regarding OPCs (Gregath and Lu, 2018 ).…”
Section: Transcriptomic Technologiesmentioning
confidence: 88%
“…Previously, numerous attempts have been made to reprogram non-muscle cells into skeletal muscle by modulating the expression of the transcription factor Myod1, which plays an important role in myogenesis [ 10 , 11 ]. 5-azacytidine (5-aza), a DNA methyltransferase inhibitor, induces demethylation of the Myod1 locus in differentiated somatic cells and increases Myod1 transcripts, leading to transdifferentiation into the myogenic lineage [ 9 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the basic region, the HLH motif of Myod1 is also required for myogenesis because the HLH motif dimerizes with other bHLH proteins, whose basic domains are involved in E-box binding [ 42 ]. The other domains are also highly conserved and have been known to be functional Myod1 domains [ 11 , 44 ]. For example, the acidic domain acts as a transcriptional activation domain (TAD) through additional DNA binding near E boxes, and both the H/C and helix3 domains are involved in chromatin remodeling to allow active transcription of sequential myogenic genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most critical part of this process is the activation and proliferation of satellite cells [34]. Studies have found that continuous activation depletes satellite cells and stagnates skeletal muscle recovery [35,36]. LF-EMF has been proven…”
Section: Low-energy Lf-emf Promotes the Late Differentiationmentioning
confidence: 99%